Histologic Characteristics of Normal Perivascular Spaces along the Optic Tract: New Pathogenetic Mechanism for Edema in Tumors in the Pituitary Region - Saeki, Naokatsu (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: Perivascular (PV) spaces are known to distend and cause edema along the optic tract (OT) in pituitary-region tumors. Interstitial fluid may be retained in PV spaces when tumors block their drainage outlets to subarachnoid spaces. However, these spaces and their outlets have not been anatomically elucidated. Our purpose was to evaluate how often large PV spaces are present along the OT and demonstrate their superficial communication points to adjacent subarachnoid spaces. METHODS: We examined serial histologic sections of 10 hemispheric blocks obtained from cadavers without cerebral abnormality. RESULTS: Large PV spaces, 0.5–1.5 mm in maximum height, were always present along the middle portion of the OT. Perforation points of the largest spaces were noted at the medial sulcus of the OT in seven hemispheres and through the OT in three. CONCLUSION: Large PV spaces are present along the middle portion of the OT. Their communication point to adjacent subarachnoid spaces was histologically demonstrated. The locations and variations of the outlet of large PV spaces explain the clinical features of edemas; these findings anatomically support the hypothesis that blockage of the outlets to subarachnoid spaces may play a role in distending the PV spaces and in causing edema in pituitary-region tumors. Only MR imaging has revealed this change; further pathologic investigations are awaited.